Hidden in plain view: an example from Ptilidium (Ptilidiaceae, Marchantiophyta) - Bakalin, Vadim; Vilnet, Anna; Klimova, Ksenia; Ma, Wen Zhang; Choi, Seung Se; Hentschel, Jörn (Phytotaxa, 2021)
Ptilidium ciliare is so common in the North Holarctic and hypothetically morphologically uniform that possible diversification may have been overlooked. Previous results however showed the presence of “cryptic” diversity within the species. In the present investigation we show: 1) this diversity is not cryptic, 2) the taxon we describe as P. himalayanum has at least a Sino-Himalayan range, and 3) it occupies a morphologically intermediate position between what has traditionally been treated as P. ciliare and P. pulcherrimum. Both latter taxa are only slightly diverged genetically, and sometimes morphological discrimination is challenging such that both are better treated as varieties or subspecies within a single species.